Tunable microwave signal generation based on an Opto-DMD processor and a photonic crystal fiber - 王涛 桑新柱 颜玢玢 艾琪 李妍 陈笑 张颖 陈根祥 宋菲君 张霞 王葵如 苑金辉 余重秀 肖峰 Alameh Kamal (Chinese physics B, 2014)
Frequency-tunable microwave signal generation is proposed and experimentally demonstrated with a dual-wavelength single-longitudinal-mode （SLM） erbium-doped fiber ring laser based on a digital Opto-DMD processor and four-wave mixing （FWM） in a high-nonlinear photonic crystal fiber （PCF）. The high-nonlinear PCF is employed for the generation of the FWM to obtain stable and uniform dual-wavelength oscillation. Two different short passive sub-ring cavities in the main ring cavity serve as mode filters to make SLM lasing. The two lasing wavelengths are electronically selected by loading different gratings on the Opto-DMD processor controlled with a computer. The wavelength spacing can be smartly adjusted from 0.165 nm to 1.08 nm within a tuning accuracy of 0.055 nm. Two microwave signals at 17.23 GHz and 27.47 GHz are achieved. The stability of the microwave signal is discussed. The system has the ability to generate a 137.36-GHz photonic millimeter signal at room temperature.